Change in Engagement in Cognitive Activity and Risk for Mild Cognitive Impairment in a Cohort of Older Adults: The Monongahela-Youghiogheny Healthy Aging Team (MYHAT) Study. (April 2018) - Hughes, Tiffany F.; Sun, Zhaowen; Chang, Chung-Chou H.; Ganguli, Mary
Abstract : Engagement in cognitively stimulating activities is gaining prominence as a potential strategy to maintain cognitive functioning in old age. In a population-based cohort of individuals aged 65+ years, we examined patterns of change in frequency of engagement in total cognitive activity (TCA), higher cognitive activity (HCA), and frequent cognitive activity (FCA) based on the Florida Cognitive Activities Scale over an average of 3.62 years, and whether these patterns were associated with incident mild cognitive impairment (MCI) during this same period. Among 867 cognitively normal participants, 129 (15%) progressed to MCI. Latent class trajectory modeling identified high and stable, slowly, and quickly declining patterns for TCA; high and stable, slowly declining, and slowing increasing patterns for FCA; and high and stable, and slowly declining patterns for HCA. Separate, adjusted Cox proportional hazard models, revealed that compared with the high, stable pattern, both slow decline [hazard ratio (HR), 2.5; 95% confidence interval (CI), 1.5-4.0] and quick decline (HR, 11.0; 95% CI, 6.3-19.2) in TCA, and slow decline in the FCA (HR, 8.7; 95% CI, 5.3-14.3) and HCA (HR, 3.4; 95% CI, 2.0-5.6) subscales increased risk for incident MCI. Maintaining engagement in cognitive activities may be protective against progression to MCI, alternatively, declining engagement may be a marker for impending cognitive impairment. Abstract : Supplemental Digital Content is available in the text.